2023
DOI: 10.3389/fpubh.2023.987362
|View full text |Cite
|
Sign up to set email alerts
|

How long can Chinese women work after retirement based on health level: Evidence from the CHARLS

Abstract: ObjectiveTo further enhance the understanding of factors impacting female participation in the workforce based on health levels and to measure the excess work capacity of middle-aged and older female groups by residence and educational level.MethodsData of women aged 45–74 were accessed from the China Health and Retirement Longitudinal Study (CHARLS) from 2011, 2013, 2015, to 2018. The health status of women was comprehensively evaluated by single health variables and frailty index. A Probit model was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…According to Moore and Kawachi (1), it is difficult for individuals to engage in reciprocity exchanges or collective action without the perception of trust. In rural China, a majority of aging adults, as well as middle-aged individuals over 50, primarily engage in agricultural activities (51). Within this context, the interviewees F1 and F2 reported that they assisted their neighbors based on a high level of mutual trust.…”
Section: "(Neighborhood Relations) Very Good Distant Relatives Are No...mentioning
confidence: 97%
“…According to Moore and Kawachi (1), it is difficult for individuals to engage in reciprocity exchanges or collective action without the perception of trust. In rural China, a majority of aging adults, as well as middle-aged individuals over 50, primarily engage in agricultural activities (51). Within this context, the interviewees F1 and F2 reported that they assisted their neighbors based on a high level of mutual trust.…”
Section: "(Neighborhood Relations) Very Good Distant Relatives Are No...mentioning
confidence: 97%
“…A study on the labor capacity of retired women in China reveals that the excess labor capacity of urban women aged 50 to 64 is 6.1–7.8 years, while that of urban women aged 50 to 74 is 9.8–14.9 years. Moreover, the excess working capacity of urban women is approximately 6 times that of rural women, and the excess working capacity of highly educated women is 3 times that of illiterate women [ 10 ], and Ulrich refers to this group of people who continue to work after reaching retirement age as “Silver workers” [ 11 ]. This kind of work is known as “bridge employment”, which serves as a link or transition between regular employment and total withdrawal from the labor market [ [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%